2001
DOI: 10.1080/10715760100300201
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of vitamins C and E on the number of micronuclei in lymphocytes in smokers and their role in ascorbate free radical formation in plasma

Abstract: Cigarette smoke is widely believed to increase free radical concentrations causing subsequent oxidative processes that lead to DNA damage and hence, to several diseases including lung cancer and atherosclerosis. Vitamin C is a reducing agent that can terminate free-radical-driven oxidation by being converted to a resonance-stabilized free radical. To investigate whether short-term supplementation with the antioxidants vitamin C and E decreases free-radical-driven oxidation and thus decreases DNA damage in smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 26 publications
3
23
1
3
Order By: Relevance
“…The antimutagenic effect involves an anticlastogenic effect of VC and its capability of decreasing the number of chromatid and chromosomal type aberrations. The lack of a genotoxic effect of ascorbic acid is consistent with other in vivo studies that have demonstrated the anti-oxidant effects of ascorbic acid (Schneider et al, 2001;Lee et al, 1998). As a cofactor in hydrolase and oxygenase enzymes, ascorbic acid maintains iron and other metals in a reduced state.…”
Section: Discussionsupporting
confidence: 77%
“…The antimutagenic effect involves an anticlastogenic effect of VC and its capability of decreasing the number of chromatid and chromosomal type aberrations. The lack of a genotoxic effect of ascorbic acid is consistent with other in vivo studies that have demonstrated the anti-oxidant effects of ascorbic acid (Schneider et al, 2001;Lee et al, 1998). As a cofactor in hydrolase and oxygenase enzymes, ascorbic acid maintains iron and other metals in a reduced state.…”
Section: Discussionsupporting
confidence: 77%
“…The supplementation resulted in an increase of both vitamin C and AFR in the plasma with a concomitant decrease of micronuclei in lymphocytes, an established marker for DNA damaging (Schneider et al, 2001). Based on these results, we had no evidence for DNA damage mediated by vitamin C and AFR.…”
Section: Introductionmentioning
confidence: 56%
“…A balance between ROS and the amount of antioxidants is essential for the normal development of embryos especially in the laboratory. Numerous studies have demonstrated the antioxidant effects of vitamin C on living cells [25]. Vitamin C was also used to prevent cytogenetic damage to the embryos that were produced by breeding irradiated male and Fig.…”
Section: Discussionmentioning
confidence: 99%